2003
DOI: 10.1167/iovs.02-1115
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Photodynamic Therapy on Expression of Vascular Endothelial Growth Factor (VEGF), VEGF Receptor 3, and Pigment Epithelium–Derived Factor

Abstract: PDT using verteporfin induces a reproducible angiogenic response in elderly human eyes. VEGF, VEGFR-3, and PEDF expression is enhanced after PDT. Choroidal endothelial cells appear to be the primary site of angiogenic stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
199
2
13

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(222 citation statements)
references
References 31 publications
7
199
2
13
Order By: Relevance
“…Similar to this study, the long-term outcomes of AMD after PDT have indicated several serious problems. For example, long-term influences of PDT, such as damage to the retinal pigment epithelium after PDT 21 and choroidal hypoperfusion (which is correlated with chorioretinal atrophy), 22 have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this study, the long-term outcomes of AMD after PDT have indicated several serious problems. For example, long-term influences of PDT, such as damage to the retinal pigment epithelium after PDT 21 and choroidal hypoperfusion (which is correlated with chorioretinal atrophy), 22 have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…12 The surge of local angiogenic factors caused by choroidal hypoperfusion, persistent inflammation from CNV itself, and following treatment may also contribute to the high rate of recurrence. 13,14 Several studies have shown that PDT combined with intravitreal injection of the corticosteroid triamcinolone acetonide (IVTA) is more effective for treating CNV than PDT alone. [15][16][17][18][19] However, IVTA has been shown to produce side effects, such as cataract progression, elevated intraocular pressure (IOP), endophthalmitis, and retinal detachment.…”
Section: Introductionmentioning
confidence: 99%
“…Local release of VEGF occurs after PDT as well. 23 This could have a detrimental effect on the CNV process when inflammation is the main mechanism.…”
Section: Discussionmentioning
confidence: 99%